BLAST-WAVE IMPULSE COMPACTION OF THE VISCOELASTOPLASTIC MOLDING SAND - Berezyuk Vladimir Grigorievich,; Kuzembayev Serik Babaevich,; Sikhimbayev Muratbay Ryzdikbayevich,; Absadykov Bakhyt Narikbayevich, (Scientific Journal of Pedagogy and Economics, 2020)
This article examines the compaction process in the green molding sand by the explosive impulse of combustion gas. The study was taken on a testing device based on the semi-automatic molding machine. The dependence of mold density on impulse power and physical and mechanical properties of the sand has been found. An explosion pressure wave drives the sand column in a flask. The sand moves gradually by layers. Each layer first accelerates, then moves uniformly, decelerates and eventually stops. Here, the layer is compacted due to the kinetic energy of its movement. The higher the velocity of the molding sand is, the higher its kinetic energy and the compressive stress gained during the compaction, are. Fluidity of the molding sand depends on its physical and mechanical properties, particularly on its viscosity. The behavior of viscous, elastic and plastic properties of the molding sand during the compaction process has been researched using the self-designed device. During the compaction process, the parameters interchange, while the value of the sum is constant. During the acceleration phase, the molding sand has minimal elastic properties, the viscous properties recede and plastic properties enhance. During the uniform motion of the sand, its viscous properties are minimal, while the plastic properties enhance to the maximum. Then till the end of the process, viscous properties keep enhancing up to 80…90 %, while plastic properties recede almost to zero. Elastic properties slightly enhance almost linearly during the whole process.